Nieznany "wywiad" Józefa Czapskiego - Piekara, Jędrzej (Colloquia Litteraria, 2020)
Józef Czapski’s ‘Interview’ from 1974 is a unique testimony from a Polish emigrant that came about so early and which concerns the Russian stage of the artist’s life. In the light of today’s knowledge, Józef Czapski’s statement is not „revolutionary” and does not change much how his relations with Russia can be perceived. However, it is a valuable supplement to the source material, which at the same time it definitely expands in some aspects. In a conversation with his friend – Michał Heller – Czapski told a story about his life in Russia, about his reading at that time – the passion of Tolstoy, Norwid and Brzozowski - about what Polish literature and Polish independence movements were to him then. The interview conducted by Michał Heller with Józef Czapski has until now been unknown in Polish (it was similarly published in the November issue of ‚Nowa Polsza’ in 2018) and was recorded on a magnetic tape in the archive of Michał Heller in the library near Nanterre in Paris. Józef Czapski began his story by describing his first years of life – his childhood in Przyłuki and then his trip to St. Petersburg to study. Czapski’s words will guide the listener / reader through the history of his turbulent stay in Russia during the First World War - through years of studying in the Cadet Corps, serving in the reviving Polish Army, and eventually leaving it and attempting to create a pacifist, mystical religious movement. This story is a perfect extension of what we know today about this period of the artist's life. of the artist’s life.